(untitled) (Bangladesh Journal of Medical Science, 2026)
Objective This review examined the acceptability, feasibility, and efficacy of spirituality-integrated interventions for carers (CGs) of terminally ill or palliative patients, as well as the components that need to be modified to meet their psychological needs better. Materials and methods The review is consistent with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria. We searched Scopus, PubMed, and Web of Science for research on spiritually integrated therapies and CGs from January 2016 to August 2025. Google Scholar and relevant article bibliographies were checked for additional qualifiers. Two researchers assessed the titles, abstracts, and full texts of prospective qualifying papers. The collective discussion resolved conflicts. The updated Cochrane Collaboration’s methodology 2.0 was employed to classify the total risk of bias (RoB) for each reviewed investigation as low risk, some concerns, or high risk. Results A search of electronic databases revealed 233 studies, and 63 duplicates were removed. This led to 170 title and abstract screening investigations. For full-text evaluation, 53 publications met the inclusion criteria. The review included 21 RCTs on spiritually integrated therapies for CGs. The evaluated studies showed that CGs participating in a spirituality-based intervention improved their emotional, physical, and spiritual well-being. Five of 21 RCTs examined using RoB 2.0 had high RoB, nine had some concerns, and seven had low RoB. Conclusion The majority of CGs indicated an enhanced feeling of spiritual wellness and better physical and mental health in caring situations in comparison to control settings. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S211-S222